In vitro regeneration of semecarpus anacardium L. from axenic seedling-derived nodal explants - Panda, Bhuban Mohan; Hazra, Sulekha (Trees-Structure and Function, 2010)
Semecarpus anacardium (Anacardiaceae), a deciduous forest tree, is a potent source of medicinal compounds. Poor seed viability of this species limits the conventional propagation practice. Proliferation of shoots from axillary meristem was achieved in semisolid WPM medium supplemented with BAP 4.44 mu M and KN 4.64 mu M. Factors including culture vessels, gelling agents and antioxidants were identified and optimized for proliferation and growth of shoots in vitro. Cotton-plugged culture vessels were more favorable. Phytagel 0.2% as gelling agent and activated charcoal 0.2% as antioxidant were superior to other agents and antioxidants tested. All the shoots rooted in half-strength WPM liquid medium with IBA 2.46 mu M. Rooted shoots survived (91%) in the soil-sand 1:1 mixture. Ex vitro rooting of shoots and hardening of plants were achieved in 80% of the explants in the soil-sand mixture. Hardened plants were maintained in a greenhouse. This is the first report on in vitro regeneration of Semecarpus anacardium.
Keywords: Antioxidants; Culture vessels; Ex vitro rooting; Gelling agents; Medicinal tree; micropropagation

In vitro morphogenic response in cotyledon explants of semecarpus anacardium L. - Panda, Bhuban Mohan; Hazra, Sulekha (Plant Biotechnology Reports, 2012)
Three different morphogenic responses-caulogenesis, direct somatic embryogenesis, and callusing-were noted in cotyledon explants of Semecarpus anacardium L. cultured in woody plant medium (WPM) containing thidiazuron (TDZ). Thidiazuron, at all concentrations tested, induced organogenic as well as embryogenic responses. The organogenic buds differentiated to shoots and the embryogenic mass (EM) gave rise to globular embryos which differentiated up to cotyledon-stage embryos on repeated culture in growth regulator (GR)-free WPM medium containing 0.2% activated charcoal after the removal of TDZ. The organogenic and embryogenic responses were optimal in 9.08 mu M TDZ after the removal of TDZ. Elongated shoots rooted in half-strength liquid WPM medium with 2.46 mu M indole butyric acid. Plants were successfully acclimatized and transferred to soil. Histological studies confirmed the direct origin of the organogenic buds from the cotyledon explants. The EMs produced somatic embryos on repeated culture in charcoal incorporated GR-free medium. Morphogenic callus formation from the cotyledon explants was also noted. This callus on repeated culture in WPM medium with charcoal differentiated into somatic embryos. Repetitive somatic embryogenesis was evident from direct and indirectly formed primary embryos. The somatic embryos did not convert into plantlets, though sporadic germination of embryos was observed through the emergence of roots.
Keywords: callus; Caulogenesis; Globular embryos; Growth regulator; Histology; somatic embryogenesis

Micropropagation of semecarpus anacardium L.: a medicinally important tree species - Panda, Bhuban Mohan; Hazra, Sulekha (Plant Biosystems, 2012)
Semecarpus anacardium L., a deciduous forest tree, is a source of medicinal compounds. Poor seed-viability restricts the conventional propagation. Micropropagation protocol is standardized for this species. Shoot culture-derived nodal explants were cultured in woody plant media supplemented with thidiazuron (TDZ). Shoot differentiation from meristem was limited. Meristems swelled to form meristematic mass in higher concentrations of TDZ. Swelling of meristem was attributed to the proliferation of meristematic cells. Development of shoots from meristematic mass on withdrawal of TDZ in culture medium indicated the inhibitory influence of TDZ on differentiation of buds to form shoots. Harvesting the primary shoot, leads to appearance of additional shoot buds which elongated on repeated transfer of explants in a medium devoid of growth regulator every four weeks. Optimum (17) number of shoots obtained from each meristem in explants pre-cultured in TDZ 2.27 mu M and re-cultured in growth regulator free medium for seven cycles (28 weeks). This confirms the stimulatory influence of TDZ on proliferation of meristem and inhibitory influence on shoot differentiation. All shoots, rooted in the medium with Indole butyric acid 2.46 mu M. Plantlets survived on transfer to sand: soil (1: 1) mixture and acclimatized. This is the first report on micropropagation of S. anacardium from seedling derived nodal buds using TDZ.
Keywords: Meristematic; micropropagation; Semecarpus anacardium L.; thidiazuron

Optimizing culture conditions for establishment of hairy root culture of semecarpus anacardium L. - Panda, Bhuban Mohan; Mehta, Urmil J.; Hazra, Sulekha (3 Biotech, 2017)
Semecarpus anacardium L. is a tree species which produces secondary metabolites of medicinal importance. Roots of the plant have been traditionally used in folk medicines. Different strains of Agrobacterium rhizogenes (A4, ATCC15834 and LBA 9402) were used for induction of hairy roots in in vitro grown tissues of the plant. Hairy root initiation was observed after 25-30 days of infection. Optimum transformation frequency of 61% was achieved on leaf explants with ATCC15834 strain. Infection time of 30 min resulted in greater transformation frequency compared to 10 and 20 min, respectively. The hairy roots cultured in growth regulator-free semi-solid woody plant medium differentiated into callus. Whole shoots infected with ATCC 15834 were found to produce more transformants upon co-cultivation for 4 (65%) and 5 (67%) days. Induction of hairy roots in stem explants infected with ATCC 15834 was lower (52%) compared to leaves (62%) after 4 days of co-cultivation. In A4 and LBA9402 strains transformation efficiency was 49 +/- 2.8% and 36 +/- 5.7% in shoots after 4 days of co-cultivation. Transformation frequency was higher in ATCC15834 strain, irrespective of explants. The hairy roots of S. anacardium elongated slowly upon transfer to half-strength liquid medium. After 3-4 passages in liquid medium slender hairy roots started differentiating which were separated from the original explants. Visible growth of the roots was observed in hormone-free liquid medium after 2-3 months of culturing. Polymerase chain reaction with gene-specific primers from rol A, B and C genes confirms the positive transformation events.
Keywords: Hairy root culture; In vitro culture; rol genes; Semecarpus anacardium; Transformation